PENGEMBANGAN E- MODUL IPS BERBASIS APLIKASI PAGE FLIP UNTUK KELAS IV SEKOLAH DASAR - Fatimah, Iis Daniati (Jurnal Tunas Pendidikan, 2022)
The teaching materials developed should be used independently and easily accessible by learners. The module becomes one form of the teaching material that can be developed because it has five main characteristics that become the strong of self-instructional (facilitating self-instructional (facilitating self-instructional (facilitating self-instructional), self mastery (loading whole materials), stand-alone (independent), adaptive, and use friendly (easy to use). It is research and developmen/r&d. The research model developed by the researcher model 4p, development goes on to define, decomposition, development and dissemination of product. The design worthiness of the module can be seen from the validation given by the design expert. The instrument used to collect data is a validation sheet. The results of data collection are analyzed using qualitative descriptive techniques. The design worthiness of the module is demonstrated through the validator of the design experts, where at stage 1 validation get a 64% percentage with sufficient criteria. Based on input and phase 1 assessments, they are revised on the module and continue validation at phase 2. As for the percentage at stage 2, it's 92% with very good criteria.